Teacher Work Stress Management from a Transactional Theory Perspective in Islamic Educational Institutions - Al Ghifari, Mahdini; Ratih Erissa Putri; Salfen Hasri; Sohiron (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Teacher work stress in Islamic educational institutions has a significant impact on the quality of learning and educator professionalism, as it is influenced by pedagogical demands, administrative burdens, and religious values perceived as a moral responsibility. This study aims to analyze the management of teacher work stress through the perspective of the Transactional Theory of Stress proposed by Lazarus and Folkman, as well as its relevance within the context of Islamic education. Using a qualitative approach through a literature review, the population comprised relevant literature up to 2025 addressing teacher work stress in Indonesia, with a purposive sample of 20–30 Sinta- and Scopus-indexed articles published between 2021 and 2025. The research instrument consisted of documentary sources, which were analyzed using the Miles and Huberman model (data reduction, data display, and data verification). The findings indicate that teacher work stress emerges from the interaction between primary and secondary appraisal processes that shape coping strategies, which are further enriched by spiritual dimensions such as patience (ṣabr) and trust in God (tawakkul) within the Islamic context. The Transactional Theory is shown to be a holistic framework capable of accommodating psychological, organizational, and religious dimensions of teacher work stress management.